BARRIERS TO FINANCIAL INCLUSION: AN ISM MICMAC ANALYSIS - Kumar, Santosh; Shukla, Gargi Pant; Dubey, Rakesh K Dhar (International Journal of Accounting & Finance Review, 2020)
The policymakers should take a series of immediate actions to address the consequences of the Covid-19 pandemic in the path of the sustainable economy by reaching to every segment of the society to return the economy on track, financial inclusion (FI) is the only way to achieve the target. The study analyzes the obstacles in the path to achieve sustainable growth, which has been partitioned into two stages; the identification of barriers and investigation. The study has divided into three diverse stages: identification of barriers, interviews with specialists from industry, and framing an ISM model. Fifteen barriers have been identified in the achievement of goals of financial inclusion with four levels in ISM designed model. Not enough money, Lack of trust, High cost, Financial Illiteracy, Gender issues, Age factor, and Terms and conditions are factors of prime importance as they have very high driving as well as dependence power. Factors like Irregular income, Distance, and Legal identity are not showing a direct impact on other variables in the system, so these three factors may overlook by decision takers. Psychological and cultural barriers and Bank charges are very important barriers to high dependent driving power. These obstacles must require proper attention.